UPAYA MENAHAN NAFSU DAN AMARAH - Zainur Rofi', Muhammad; Hasanah, Uswatun (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2023)
There are two important elements in the human soul. He then determines the potential of the people who play a role, namely Rabb and lust. Lust always requires action that goes beyond limits, following and prioritizing mere desires. To fight lust is very difficult because lust is within human self, which flows with blood and controls the entire human body itself. Lust usually leads to things that are bad, immoral, and tyrannical. According to Imam Al-Ghazali, lust is the meaning of gathering strength, anger and lust in humans. That's why sometimes Lust also causes anger in humans. Anger is actually not something that must be eliminated in humans, it only needs to be controlled so that it does not go beyond the limit. According to Imam Al-Ghazali, anger is like a burning flame that blazes, which attacks and agitates in the human heart. In order to prevent anger in humans Al-Imam Al-Ghazali as quoted by Sheikh Jamalud din Al-Qasimi explained that when anger peaks, there are two ways that the outburst of emotion can be soaked up, namely by knowledge and by charity